2023
DOI: 10.1186/s13020-023-00746-4
|View full text |Cite
|
Sign up to set email alerts
|

Berberine improves negative symptoms and cognitive function in patients with chronic schizophrenia via anti-inflammatory effect: a randomized clinical trial

Abstract: Background Based on the neuroinflammation hypothesis in schizophrenia and known anti-inflammatory effects of berberine, the aim of the present study is to investigate the efficacy of berberine in treating negative symptoms and cognitive deficits in adult patients with chronic schizophrenia. Methods Enrolled participants were randomized to receive berberine or placebo for 3 months. The Scale for the Assessment of Negative Symptoms (SANS), Trail-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Berberine as a potent antioxidant improves diabetes and protects against nephropathy and other metabolic syndrome-associated kidney diseases (33)(34)(35). The antioxidant properties and anti-inflammatory effects of berberine cause a decrease in the negative symptoms in neuropathic patients (36,37). Studies have shown that berberine has also a potent effect on lung damage and other pulmonary inflammations (38)(39)(40).…”
Section: Resultsmentioning
confidence: 99%
“…Berberine as a potent antioxidant improves diabetes and protects against nephropathy and other metabolic syndrome-associated kidney diseases (33)(34)(35). The antioxidant properties and anti-inflammatory effects of berberine cause a decrease in the negative symptoms in neuropathic patients (36,37). Studies have shown that berberine has also a potent effect on lung damage and other pulmonary inflammations (38)(39)(40).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, immune regulation involving PD-1/PDL-1 and TLR4/NF-κB is associated with baicalin’s ability to alleviate hepatocellular carcinoma, UC, and CRC [ 130 ]. Berberine, a key compound found in medicinal plants like Coptis chinensis (Huanglian) or Cortex phellodendri (Huangbo), has demonstrated safety and efficacy in reducing CRC recurrence and inhibiting its progression [ 139 ]. Berberine also enhances beneficial short-chain fatty acids, reduces fecal LPS content, upregulates intestinal barrier biomarkers, and inhibits the TLR4/NF-κB P65/IL-6/p-STAT3 pathway.…”
Section: Tcms With Anti-crc Effects Through Tlr4 Signaling Pathwaymentioning
confidence: 99%